ANALISIS MUTU BERAS (Oryza sativa L.) VARIETAS SITU BAGENDIT PADA PERLAKUAN PENGERINGAN DAN FREKUENSI PENGGILINGAN YANG BERBEDA - Aris, Iwan Sarjono; Pamungkas, Djoko Heru; Widata, Sri (Universitas Sarjanawiyata Tamansiswa, 2018)
This research was to determine the effect of drying treatment and milling frequency on the yield and physical quality of rice situ bagendit varieties. This research was conducted in jogonalan sub-district, Klaten Regency. The area is located at an altitude of 114 masl and is included in the lowlands, then has an average rainfall of 8mm-350mm every month. The average air temperature is 280-300 C with 153mm/s wind speed every month and has regosol soil type. This research was conducted in August-September 2018, using a 3x3 factorial trial design arranged in a Randomized Complete Block Design (RCBD). The first factor is the drying time which consists of 3 levels, namely drying 10 hours, 20 hours and 30 hours. The second factor is the grinding frequency which consists of three levels, namely grinding once, grinding twice, and grinding three times. Each experimental unit was combined and repeated as many as three replications. Observation variables included the percentage of grain and rice moisture content, milled yield, percentage of head rice, broken rice, menir rice, limestone grains, grain grains, weight of husks and bran, as well as the degree of social value. The results of the data analysis showed an interaction between the two experimental factors on the percentage of rice moisture content, milled yield, broken lime grains, whole rice, menir rice, broken rice, husk weight, and milling degree. The treatment of drying for 20 hours and the frequency of milling three times showed the highest yield, then on the physical quality of rice the combination of 20 hours of drying treatment and one-time grinding showed the highest yield of whole rice